Stress in farmers: a survey of farmers in England and Wales. Issue 11 (November 1998) - Simkin, S; Hawton, K; Fagg, J; Malmberg, A
Abstract : OBJECTIVES: To investigate potential sources of stress for farmers in England and Wales METHOD: A postal questionnaire was sent to a randomly selected group of 800 members of the National Farmers' Union and 200 members of the Farmers' Union of Wales. RESULTS: 500 questionnaires (51%) were returned completed between October 1995 and March 1996. Farmers had problems with record keeping and paperwork (62%), difficulty understanding forms (56%), and problems arising from the effects of new legislation and regulations (49%). Nearly a quarter (23%) reported financial problems and most worried about money (79%). Very few were socially isolated, with over 90% having at least one confidant. 70% worked > 10 hours a day, and 31% had health problems which interfered with their work, including more than a quarter of those < 50. 16% of the sheep farmers reported symptoms which they attributed to organophosphate poisoning. The farmers most vulnerable to financial and other problems were those with small farms and mixed farming operations. Farmers in Wales also seemed more vulnerable than those in England, but a lower response rate from members of the Farmers' Union of Wales means this difference should be interpreted cautiously. CONCLUSION: The survey confirms findings from several regional studies that many farmers are experiencing considerable stress from various causes. Local and national initiatives to assist farmers, including outreach programmes, should be encouraged. Policy makers should be aware of the potential impact of legislation, particularly on the more vulnerable groups.